Minimal deviation adenocarcinoma and its mimickers: a case report with review of literature - Jain, Manjula; Agarwal, Savita; Malhotra, Sonal (Annals of Pathology and Laboratory Medicine, 2015)
Amongst all the glandular lesions of the cervix, minimal deviation adenocarcinoma (MDA) the, so called Adenoma-malignum and its mimickers have been the subject of great interest in the literature. Although a rare entity, MDA commonly requires consultancy to distinguish it from many benign cervical glandular lesions. MDA is a unique neoplasm of the uterine cervix, characterized by mucinous glands with deceptively benign histological appearance posing difficulty in its diagnosis. In the present case report MDA was an incidental finding in a 45 year old female, on the hysterectomy specimen submitted for multiple leiomyomas, and the diagnosis was based on histopathological and immunohistochemical (IHC) findings.